A contribuição do Instituto Federal de Sergipe para o desenvolvimento regional - Nascimento, João Ricardo Almeida do (2020)
According to Law 11.892 / 2008, one of the purposes of the Federal Education Institutes is to offer professional and technological education, at all levels and modalities, training and qualifying citizens with a view to professional performance in the various sectors of the economy, with emphasis on local, regional and national socioeconomic development. In this sense, the present research had as main objective to analyze the contribution of the Federal Institute of Sergipe in the formation of human capital to attend the demands for qualified labor of the great economic sectors of Sergipe and the micro-regions where it operates. To this end, a bibliographic survey was carried out on the subject of human capital, growth and economic development. Then, a study was carried out on the dynamics of the economic and social development of the State of Sergipe and its micro-regions, verifying the extent to which there was a relationship between professional and technological education and the development indicators of these locations. For this purpose, the analysis of the Locational Quotient Index (QL) of Sergipe and the micro-regions was used, based on the data of the formal jobs existing in the years 2002, 2010 and 2017, through RAIS (from the former MTE); the types of courses offered by IFS, with data from the Nilo Peçanha Platform (MEC) and the composition of Sergipe's GDP by the major productive sectors of the economy: agriculture, industry and services, based on data collected from the Sergipe Observatory (Government of Sergipe ) and the Brazilian Institute of Geography and Statistics (IBGE). Through the correlation and analysis of the data found, the work showed the existence of alignment between the offer of Professional and Technological Education - EPT (IFS) and the economic and social development of Sergipe and its micro-regions.